A Faculty Learning Community Implements Research-based Curriculum and Pedagogy to Redesign Precalculus. Issue 5 (28th May 2023) - Hower, Jeremiah; Merkin, Roneet; Wells, Leanne
ABSTRACT: This article reports on a reconceptualization of the Precalculus course experience at Florida International University. We discuss the details of the redesign process – unified within a faculty learning community (FLC) model – along with a broader change in the course sequence leading up to Calculus. We provide data, including the comparison between the treatment and control groups.